(untitled) (Progressive Agriculture, 2021)
The experiment was conducted during rabi season 2019-2020 at Agricultural Research Station, On Farm Research Division, Alamnagar, Rangpur to find out the useful effects of organic fertilizer on growth and yield of tomato. The experiment was arranged in a randomized complete block design (RCBD) with five treatments in three (03) compacted replicate blocks. The treatments included T1: 100% Recommended Chemical Fertilizer (RCF), T2: 85% CF + 3 tha-1 organic Fertilizer (OF), T3: 85% CF + 1 tha-1 OF, T4: 70% CF + 3 tha-1 OF and T5: 70% CF + 1 tha-1 OF. The highest yield was observed in T2 (50.59 t ha-1) due to more number of fruit plant-1& weight of fruit plant-1 and the lowest was in T5 (35.32 t ha-1). These results may be due the parameters of growth components increased with increasing amount of organic and inorganic fertilizers applied. Combination of organic and inorganic fertilizer treated plots produced higher yield than plots without combination of organic and inorganic fertilizer. The highest gross return (BDT. 607080) was found in T2 treatment and the lowest gross return (BDT. 423840) was recorded from T5. The highest gross margin (BDT. 328520 ha-1) was obtained from T2. The lowest gross margin (Tk. 145280 ha-1) was obtained from T5. Integrated nutrient management (combination of organic and inorganic fertilizer) is the best option for higher tomato production in Bangladesh. Progressive Agriculture 32 (1): 10-16, 2021